Optimal performance fees and flow of funds in asset management contracts - Yoshima, Samy Osamu Abud (2006)
This paper investigates the importance of ow of funds as an implicit incentive in the asset management industry. We build a two-period binomial moral hazard model to explain the trade-offs between ow, performance and fees where effort depends on the combination of implicit (flow of funds) and explicit (performance fee) incentives. Two cases are considered. With full commitment, the investor's relevant trade-off is to give up expected return in the second period vis-à-vis to induce effort in the first period. The more concerned the investor is with today's pay- off, the more willing he will be to give up expected return in the second period by penalizing negative excess return in the rst period. Without full commitment, the investor learns some symmetric and imperfect infor- mation about the ability of the manager to obtain positive excess return. In this case, observed returns reveal ability as well as effort choices. We show that powerful implicit incentives may explain the flow-performance relationship with a numerical solution. Besides, risk aversion explains the complementarity between performance fee and ow of funds.